Landfill Leachate Treatment with Ozonation to Improve Biodegradability - Junaidi Junaidi; Wiharyanto Oktiawan; Komang Dewi Novianti (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
Leachate is a liquid that comes from processed waste generation so that it contains compounds that are harmful or toxic to the environment. The quality of the leachate obtained included COD: 3,315 mg/l, BOD: 339 mg/l, TSS: 216 mg/l, and color 3,1210 Pt.Co. Waste processing site Temesi has a BOD/COD ratio of 0.11, this value is not suitable for using biological treatment because the biodegradability value is small so it is difficult for microorganisms to degrade existing pollutants. Therefore, it is necessary to have an pretreatment that is used to increase the value of biodegradability, one of which is oxidation using ozone. Ozone has a strong oxidizing value so that it can produce free radicals to break long chains of pollutants so that they become simpler. This research on ozone oxidation resulted in an increase in the BOD/COD ratio from 0,1 to 0.14 with a generator capacity of 36 g/hour. In this study, an ozone generator of 100 G/hour was used which increased the BOD/COD ratio to 0.46 with a final COD yield of 815 mg/l increasing BOD to 379 mg/l, TSS become 157,62 mg/L and color become 23.642 Pt.Co.